Girls who code : learn to code and change the world - Saujani, Reshma (Viking, an imprint of Penguin Random House LLC, 2017)
Introduces the relevance of coding and shares down-to-earth explanations about coding principles and real-life stories of women programmers who work at such places as Pixar and NASA.